2004
DOI: 10.2190/09gb-wu04-vtv7-v0fl
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Factors Affecting Contraception and Fertility in Bangladesh

Abstract: Using the data derived from the 1989 Bangladesh Fertility Survey, the 1993-94 and 1996-97 Bangladesh Demographic and Health surveys, this study attempts to find the relationships between the factors affecting contraception and fertility among currently married women by using a linear recursive path model which provides direct and indirect relationships between the variables. The results suggest that women's status had a significant negative effect on childbearing and it had a significant positive effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…Specifically, when women’s agency is measured as participation in household decision-making and mobility, women with greater agency are, in fact, more likely to have had a birth and have a greater total number of births. These results are counter to some previous studies, primarily in other countries, which point to an inverse relationship between agency and fertility (Hindin 2000; Kabir, Ibrahim and Kawsar 2005; Khan and Raeside 1997) or to non-significant associations between agency and fertility (Abadian 1996; Malhotra et al 1995). A few studies are consistent with these findings and have found positive associations (Amin, Hill and Li 1995; Sathar and Kazi 1997; Upadhyay and Karasek 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, when women’s agency is measured as participation in household decision-making and mobility, women with greater agency are, in fact, more likely to have had a birth and have a greater total number of births. These results are counter to some previous studies, primarily in other countries, which point to an inverse relationship between agency and fertility (Hindin 2000; Kabir, Ibrahim and Kawsar 2005; Khan and Raeside 1997) or to non-significant associations between agency and fertility (Abadian 1996; Malhotra et al 1995). A few studies are consistent with these findings and have found positive associations (Amin, Hill and Li 1995; Sathar and Kazi 1997; Upadhyay and Karasek 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Most studies ( n = 29) analyzed the number of children either ever born or born within a specific period for individual women (Adak and Bharati, 2011; Al Riyami and Afifi, 2003a, 2003b; Ali et al, 1995; Ali and Sultan, 1999; Amin et al, 1995; Audinarayana, 1997; Balk, 1994; Bates et al, 2007; Goni and Saito, 2010; Gwako, 1997; Hari, 1991; Hindin, 2000; Hirschman and Guest, 1990; Jejeebhoy, 1991; Jin, 1995; Kabir et al, 2005a, 2005b; Khan and Raeside, 1997; Kravdal, 2001; Larsen and Hollos, 2003; Manzoor and Mahmood, 1993; Muhammad and Fernando, 2010; Sathar and Kazi, 1997a; Singh et al, 2002; Steele et al, 1998; Upadhyay and Karasek, 2012; Vlassoff, 1991; Yabiku et al, 2010). Five studies looked at district-level (Aghajanian, 1992; Bhattacharya, 1998, 2006; Malhotra et al, 1995; Wasim, 2002), and four at country-level (Abadian, 1996; Sanderson, 2001; Sanderson and Dubrow, 2000; Wickrama and Lorenz, 2002) fertility rates.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies found significant inverse associations between women’s empowerment and number of children (Audinarayana, 1997; Bhattacharya, 1998, 2006; Hari, 1991; Hindin, 2000; Jin, 1995; Kabir et al, 2005a, 2005b; Khan and Raeside, 1997; Manzoor and Mahmood, 1993) while 22 yielded a combination of significant inverse findings and non-significant associations suggesting that the relationship across all empowerment domains is not always consistent or clear (Abadian, 1996; Aghajanian, 1992; Al Riyami and Afifi, 2003a, 2003b; Ali et al, 1995; Ali and Sultan, 1999; Amin et al, 1995; Balk, 1994; Bates et al, 2007; Booth and Duvall, 1981; Goni and Saito, 2010; Gwako, 1997; Hirschman and Guest, 1990; Kravdal, 2001; Larsen and Hollos, 2003; Malhotra et al, 1995; Muhammad and Fernando, 2010; Sanderson, 2001; Sanderson and Dubrow, 2000; Singh et al, 2002; Steele et al, 1998; Vlassoff, 1991; Wasim, 2002; Wickrama and Lorenz, 2002). For example, Abadian (1996) used the 1992 World Demographic Report on 54 countries to analyze whether three empowerment measures: female age at marriage, age difference between spouses, and female secondary education were associated with total fertility rates.…”
Section: Resultsmentioning
confidence: 99%
“…However, women's empowerment has been found to be consistently and positively associated with other family planning outcomes, including past use of contraception, intention to use contraception in the future, and spousal communication regarding family planning (Prata et al 2017). For example, the measures consistently positively associated with past use of contraception were education (Gage 1995, Hindin 2000, Kabir et al 2005, employment (Hindin 2000, Kabir et al 2005, household decision-making (Woldemicael 2009), reproductive decision-making (Saleem & Pasha 2008), financial autonomy (Gage 1995, Sathar & Kazi 1997, marital characteristics (Gage 1995, Hindin 2000, spousal communication (Kabir et al 2005, Woldemicael 2009), and empowerment composite scores (Ahmed et al 2010). However, reliance on retrospective data in measuring past use of contraception reduces our confidence in generalizing from these studies since empowerment may be both a cause and a consequence of contraceptive use.…”
Section: Empirical Research Using Women's Empowerment As a Predictor ...mentioning
confidence: 99%